Biomarkers of Chemotherapy-Induced Peripheral Neuropathy: Current Status and Future Directions - Rodwin, Rozalyn L.; Siddiq, Namrah Z.; Ehrlich, Barbara E.; Lustberg, Maryam B. (Frontiers in Pain Research, 2022)
Chemotherapy induced peripheral neuropathy (CIPN) is an often severe and debilitating complication of multiple chemotherapeutic agents that can affect patients of all ages, across cancer diagnoses. CIPN can persist post-therapy, and significantly impact the health and quality of life of cancer survivors. Identifying patients at risk for CIPN is challenging due to the lack of standardized objective measures to assess for CIPN. Furthermore, there are no approved preventative treatments for CIPN, and therapeutic options for CIPN remain limited once it develops. Biomarkers of CIPN have been studied but are not widely used in clinical practice. They can serve as an important clinical tool to identify individuals at risk for CIPN and to better understand the pathogenesis and avenues for treatment of CIPN. Here we review promising biomarkers of CIPN in humans and their clinical implications.